2014
DOI: 10.17138/tgft(2)254-261
|View full text |Cite
|
Sign up to set email alerts
|

Root development and soil carbon stocks of tropical pastures managed under different grazing intensities

Abstract: Grasslands may act as a carbon (C) sink or C source depending on how they are managed. Soil C stocks, root biomass, root length, root length density and soil organic C concentrations were assessed on pastures of elephant grass (Pennisetum purpureum) managed under different post-grazing stubble heights and signal grass (Brachiaria decumbens) managed under different stocking rates. Soil samples were collected in 20-cm layers down to 1-m soil depth. Neither stubble height nor stocking rate had any significant eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 19 publications
0
22
0
3
Order By: Relevance
“…These results indicate the benefits of integrating this forage with corn, with increases of 13% in TOC and 9% in TN in the uppermost soil layer, when compared to sole U. humidicola. Corn fertilization may have increased forage root development -which, in some species, can reach up to 4 Mg ha -1 in the 0.00-0.40-m layer (Saraiva et al, 2014) -and affected soil TOC and TN. Moreover, under NT systems, corn roots, which are more concentrated in surface soil layers (Silva et al, 2000), together with the deposition of plant residues, may have also contributed to increases in TOC and TN.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate the benefits of integrating this forage with corn, with increases of 13% in TOC and 9% in TN in the uppermost soil layer, when compared to sole U. humidicola. Corn fertilization may have increased forage root development -which, in some species, can reach up to 4 Mg ha -1 in the 0.00-0.40-m layer (Saraiva et al, 2014) -and affected soil TOC and TN. Moreover, under NT systems, corn roots, which are more concentrated in surface soil layers (Silva et al, 2000), together with the deposition of plant residues, may have also contributed to increases in TOC and TN.…”
Section: Resultsmentioning
confidence: 99%
“…In NTS, the absence of soil movement in association with crop rotation and above-ground dry matter may contribute to increase the LC in the first layer (0-5 cm depth) of soil depth. As reported by Saraiva et al (2014), the highest carbon stocks in the soil surface (0-5 cm depth) is due to the deposition of cover crops in association with the root system concentrated into the first layers of soil. Nevertheless, it is possible to observe that in NTS, the fertilization in the seeding row with deposition of fertilizer in 8 cm depth promotes higher concentration of roots in this depth due to the nutrients placed, this fact increased the SOM in 5-10 cm depth as it was possible to observe in this research, this way, no significant difference was observed between 0-5 cm and 5-10 cm depth (Fig 3).…”
Section: Labile Carbon In Soil Within the Top 20 CM Depthmentioning
confidence: 59%
“…In the 0.10-0.20 and 0.20-0.30-m soil layers, during the rainy season of February 2014, the levels of MBC were also higher in the ICLS, when compared with the ICLFS and native cerrado. This could be a consequence of the increased root development of Urochloa sp., which can reach 4 Mg ha -1 down to 0.40-m depth (Saraiva et al, 2014). Plant residues from eucalyptus release toxic compounds that can inhibit the growth of microbial biomass and its adaptation to the plant rhizosphere (Behera & Sahani, 2003;Araújo et al, 2010).…”
Section: Resultsmentioning
confidence: 99%